Value-Oriented English Language Learning in Higher Education - Guo, Binghua (Didactica Danubiensis, 2026)
The paper explores value-oriented English language learning as a pedagogical approach that integrates linguistic competence with the formation of ethical, cultural, and social values in higher education. In the context of globalization and intercultural academic mobility, English language education extends beyond functional communication, requiring a value-based framework that fosters critical thinking, empathy, and intercultural responsibility. The study argues that language learning environments can serve as spaces for value construction through dialogic interaction, reflective practices, and culturally meaningful content. Drawing on contemporary perspectives in educational axiology and communicative language teaching, the paper examines how value-oriented learning supports learner autonomy, social engagement, and lifelong learning competences. Particular attention is given to the role of educators as facilitators of value awareness and to the selection of learning tasks that encourage ethical reflection and intercultural dialogue. The conclusions highlight the contribution of value-oriented English language learning to the development of holistic learner profiles and to the creation of inclusive academic communities that respect diversity and promote shared values within higher education.